KONSELING KELOMPOK DENGAN TEKNIK SELF-INSTRUCTION UNTUK MENGURANGI KECEMASAN BELAJAR - Mafirja, Sulma (LPPM STKIP PGRI Bandar Lampung, 2020)
Academic anxiety is one of the concerns related to academics, where academic anxiety is anxiety related to learning problems, classes and axaminations are considered important to be discussed because, if students experiencing excessive anxiety can result in students learning motivation decreasing, and decline in learning principle that students themselves. Self-instruction is one of the techniques in the CBR approach, self-instruction is giving instructions at the beginning of how someone should respond to certain situations. Talk to yourself to become a reminder to behave appropriately. This is a strategy that is quite effective for individuals who have bad behavior. Furthermore, the self-istruction technique will be carried out by using group counseling services. Based on the results obtained, group counseling with self-instruction techniques is effective in reducing learning anxiety